2023
DOI: 10.1002/jmv.28848
|View full text |Cite
|
Sign up to set email alerts
|

Traceability of SARS‐CoV‐2 transmission through quasispecies analysis

Abstract: During COVID‐19 pandemic, consensus genomic sequences were used for rapidly monitor the spread of the virus worldwide. However, less attention was paid to intrahost genetic diversity. In fact, in the infected host, SARS‐CoV‐2 consists in an ensemble of replicating and closely related viral variants so‐called quasispecies. Here we show that intrahost single nucleotide variants (iSNVs) represent a target for contact tracing analysis. Our data indicate that in the acute phase of infection, in highly likely transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Consensus genomic sequences of SARS-CoV-2 variants represent the genomes most frequently found in the clinical samples of patients, which have been widely used to monitor the global spread of the virus during the COVID-19 pandemic ( Colson et al, 2023 ; Messali et al, 2023 ). However, these genomes represent the most frequently observed viral genomes and do not capture the full extent of their diversity ( Colson et al, 2023 ).…”
Section: Evolution and Mutationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consensus genomic sequences of SARS-CoV-2 variants represent the genomes most frequently found in the clinical samples of patients, which have been widely used to monitor the global spread of the virus during the COVID-19 pandemic ( Colson et al, 2023 ; Messali et al, 2023 ). However, these genomes represent the most frequently observed viral genomes and do not capture the full extent of their diversity ( Colson et al, 2023 ).…”
Section: Evolution and Mutationmentioning
confidence: 99%
“…With advancements in sequencing techniques, studies have reported intrahost genetic diversity of SARS-CoV-2 in specific patient groups such as immunocompromised individuals, chronically infected patients, those treated with monoclonal antibodies targeting the spike protein, and within different body compartments of a single patient ( Colson et al, 2023 ). This suggests that SARS-CoV-2 infections consist of a population of closely related viral variants, referred to as quasispecies ( Colson et al, 2023 ; Messali et al, 2023 ).…”
Section: Evolution and Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they also provide valuable insights into intrahost diversity, enabling the identification of intra-host single nucleotide variants (iSNVs) that are key in exploring hypotheses around VOC emergence. Despite the considerable size and breadth of available NGS libraries, the existing body of research on iSNV analysis remains limited, with the majority of studies focusing on a relatively small number of NGS libraries Sun et al 2023;Messali et al 2023;Xi et al 2023;Sun et al 2023;Armero et al 2021;Wertheim et al 2022;Sonnleitner et al 2022;Zhang et al 2022;Quaranta et al 2022. This gap in research can also be attributed to challenges related to data quality, such as the presence of sequencing artifacts that introduce errors and lead to false iSNVs.…”
Section: Introductionmentioning
confidence: 99%